Pelvic Organ Prolapse Repair with and without Concomitant Burch Colposuspension in Incontinent Women: A Randomised Controlled Trial with at Least 5-Year Followup - Elisabetta Costantini; Massimo Lazzeri; Vittorio Bini; Michele Del Zingaro; Emanuela Frumenzio; Massimo Porena (Obstetrics and Gynecology International)
The aim of this study was to reevaluate and update the followup of a previously published randomized controlled trial (RCT) on the impact of Burch Colposuspension (BC), as an anti-incontinence procedure, in patients with UI and POP, who underwent POP repair. Forty-seven women were randomly assigned to abdominal POP repair and concomitant BC (24 patients; group A) or POP repair alone without any anti-incontinence procedure (23 patients; group B). Median followup was 82 months (range 60–107); from over 47 patients, 30 reached 6-year followup. Two patients were lost at followup. In group A, 2 patients showed a stage I rectocele. In group B, 2 patients had a stage I rectocele and 1 a stage II rectocele. In group A, 13/23 (56.5%) were still incontinent after surgery compared with 9/22 patients (40.9%) in group B (P=0.298). No significant changes were observed between the first and the current followup. The update of long-term followup confirmed that BC did not improve outcome significantly in incontinent women when they undergo POP repair.